Anaerobic digestion of cyanobacteria and chlorella to produce methane for biofuel - Jegede, Abiodun (International Journal of Agricultural and Biological Engineering, 2012)
The methane potentials of cyanobacteria and chlorella have been investigated in eight different lab scale reactors at 25